A review on abandoned construction projects: causes & effects - Yunus, Riduan; V. Doraisamy, Sunitha; Akasah, Zainal Abidin (Trans Tech Publications, 2015)
In some countries quite a number of construction projects that are either not completed or out rightly abandoned. This paper is an overview on abandoned construction projects, and the causes and effects due to the formidable situation relating to this issue. This was conducted referring to the studies and findings in the thesis and journals on abandoned projects. Few probable causes and effects are identified from various researchers based on studies conducted by them on this issue. It is found that most of the studies on the related matter was conducted mainly using questionnaires and also by conducting interviews with the relevant parties. There were various probable causes and implications that was identified from the studies and analysis that was carried out, which does not differ much from one another, and in fact some have suggested the mitigation measures for this issue. After reviewing the research and studies that has been conducted on the issue of abandoned projects, as a conclusion, it is notable to have a more thorough investigation on the existing problem up to this date and look into the whole issue from different aspects in depth.